Hubungan Pola Asuh dengan Perkembangan Sosio Emosional pada Masa Kanak-kanak Awal - Susanti, Rini Dwi (PIAUD Universitas Islam Negeri Sunan Kudus, 2015)
Social development of children is influenced by the treatment process orguidance of parents of children in introducing aspects of social life, or the norms ofpublic life and to encourage and provide an example to their children how to applythese norms in everyday life. The application of a good family asu impact on socioemotionaldevelopment of children. Some things that affect the socio-emotionaldevelopment of children, among others; patterns of parenting, relationships withsiblings and birth order, relationships with peers, games and watching television.